Hedysarum polysaccharides mediated green synthesis of gold nanoparticles and study of its characteristic, analytical merit, catalytic activity. (January 2021) - Chen, Xinyue; Xue, Zhiyuan; Ji, Jiahui; Wang, Donghan; Shi, Gengen; Zhao, Lianggong; Feng, Shilan
Graphical abstract: Highlights: HPS-AuNPs was first green synthesized with Hedysarum polysaccharides. The synthetic mechanism was deeply explored through the comparison. This provided sensitive and selective optical sensor for Fe3+ among metal ions. HPS-AuNPs was successfully applied in spiked tap water with a wide range and low LOD. HPS-AuNPs exhibited excellent catalytic activity in the reduction of 4-nitrophenol. Abstract: We reported an eco-friendly, rapid and easy method for the green synthesis of gold nanoparticles (AuNPs) using Hedysarum polysaccharides (HPS) extracted from Radix Hedysari . To deeply explore the synthetic mechanism, the monosaccharides that made up HPS and other Radix Hedysari extract were also used as reductant to synthesize AuNPs. A series of techniques were conducted to confirm the formation of HPS-AuNPs. Moreover, as a sensitive optical detector, the large-sized HPS-AuNPs was used to selectively detect iron ion (Fe 3+ ) among the other metal irons and was successfully applied in the tap water detection with a wide range of 1 μM to 10 mM, a low detection limit of 0.57 μM. Besides, the catalytic activity of HPS-AuNPs was also proved to be well in the reduction of 4-nitrophenol to 4-aminophenol by NaBH4 . This is the first report for the green synthesis of HPS-AuNPs, providing a sensitive detector and a well-active catalyst.